Measuring, modeling and simulating the re-adaptation process of the human visual system after short-time glares in traffic scenarios - Meyer, Benjamin (Writer on vision) (Springer, 2016)
Benjamin Meyer performs several psycho-physical experiments to measure the re-adaptation process of glared drivers in traffic scenarios. The author then develops a novel tone mapping algorithm to simulate the recurring contrast perception of the human eye by adjusting the displayed contrast. Depending on background illumination, bright light sources cause considerable perception restrictions for a glared viewer and can deter the driver from perceiving critical objects for several seconds and severely increase the risk of accidents. Based on the results of the conducted user studies, this vision impairment is integrated into a night driving simulator. The modified driving simulation provides a more realistic visualization and enables the analysis of critical traffic scenarios including short-time headlight glares. This leads to better transferability of driving simulator results and enables investigating driving behavior in the presence of glare.
Keywords: Vision -- Research.; Headlight glare.; Motor vehicle drivers.; elektronické knihy; electronic books